Innowacyjność przedsiębiorstw województwa lubuskiego w świetle badań ankietowych - Nowińska-Łaźniewska, Ewa (Innovativeness of Enterprises on the Polish-German Border in the Light of the Theory of Regional Development, 2006)
Modern concepts of regional development connected with such features as those of forming networks, clusters of enterprises, etc. assume that creating the best conditions for innovative regional development is possible only by the union of forces of various types of its participants: such as their enterprises, self-government, supporting institutions and research institutions. The lack of these pro-innovational mechanisms in Poland, however, is causing a situation where enterprises do not introduce innovations on the expected scale. It should be underlined that the level of the innovativeness of the enterprises is varied. Indeed, in this context, the Lubuskie voivodship analysed from the point of view of its innovativeness is placed at the lowest position in the ranking list. The article is based on the results of (our own) research into over 50 enterprises on the Polish-German border. The author analyses the egzogenic and endogenic factors of the innovativeness and the competitiveness of the enterprises in the Lubuskie voivodship in relation to modern theories of regional development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 54-64